2014
DOI: 10.4103/0974-9233.142276
|View full text |Cite
|
Sign up to set email alerts
|

An unusual ocular emergency in severe dengue

Abstract: Dengue, one of the most common mosquito-borne flavivirus diseases affecting humans, is spread by the Aedes aegypti mosquito. Most people infected with dengue virus are asymptomatic or only have mild symptoms such as an uncomplicated fever; few have more severe features, while in a small proportion it is life-threatening. Severe dengue is defined as that associated with severe bleeding, severe organ dysfunction, or severe plasma leakage. Ophthalmic manifestations can involve both the anterior and posterior segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
3
10
0
Order By: Relevance
“…[15,16] Other very rare associations are ptosis and periorbital ecchymosis and globe rupture. [3,17,18] Our study is similar to that by Kapoor et al [15] and Hussain et al [3] with regard to male preponderance. The mean age group of our study is 32 years that is also similar in other studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[15,16] Other very rare associations are ptosis and periorbital ecchymosis and globe rupture. [3,17,18] Our study is similar to that by Kapoor et al [15] and Hussain et al [3] with regard to male preponderance. The mean age group of our study is 32 years that is also similar in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…The onset of ocular manifestations in our study correlated with the nadir of thrombocytopenia as seen in other studies. [3,9,13,18] The most common ocular manifestation in our patients was subconjunctival hemorrhage followed by retinal hemorrhages. It was similar to the studies by Kapoor et al [15] and Hussain et al; [3] however, in contrast, one patient presented with optic neuropathy in our study.…”
Section: Discussionmentioning
confidence: 70%
“…The vitreous, suprachoroidal and retrobulbar hemorrhage could have multiple probable mecahnisms, including occurred spontaneous hemorrhage [10] due to thrombocytopenia and/or due to trauma from vigorous rubbing of the eye. There has been one case report [11] of ruptured globe following proptosis, as seen in our patient. However, ruptured globe following proptosis secondary to retrobulbar hemorrhage with a normal platelet count in the conalescent phase of dengue fever, as seen in our patient, has been hitherto unreported.…”
Section: Discussionsupporting
confidence: 53%
“…Like ZIKV, dengue virus (DENV) can also cause ocular pathology, leading to the emergence of a new terminology "dengue eye disease" [56]. Clinical studies have shown that DENV can cause retinochoroiditis, vasculitis, choroidal neovascularisation, subconjunctival hemorrhage, ecchymosis, retinal artery occlusion, and in some unusual cases even globe rupture [56,57]. However, DENV infection in cornea is rarely reported.…”
Section: Introductionmentioning
confidence: 99%